Penguatan Pendidikan Karakter Melalui Bimbingan Konseling DI SMA Negeri 1 Kalabahi - Apriantyningsih, Endang; Wurianto, Arif Budi (Jurnal Kebijakan dan Pengembangan Pendidikan, 2017)
Abstract: This study aims to determine (1) the role of counseling guidance teachers in reinforcing character education. (2) the obstacles faced by counseling guidance in providing reinforcement. (3). counseling guidance efforts to overcome obstacles in reinforcing Kalabahi 1 High School. This research uses the descriptive qualitative method. The subjects of this study were counseling guidance teachers, principals, and students. Data collection techniques used were observation, interviews, and documentation. Data were analyzed using steps of data reduction, data display, and concluding. Data validity checking techniques using source triangulation. The results showed that (1) The role of the counseling guidance teacher in strengthening character education starts from planning the activities of providing guidance services, implementing the guidance and counseling program by implementing a form of service and evaluating the guidance and counseling service program. (2) Constraints faced are lack of cooperation between components in schools, lack of cooperation between BK teachers and parents/guardians, lack of voluntary teacher guidance and counseling in carrying out their duties and responsibilities, lack of honesty or openness from students on problems encountered. (3) Efforts are made namely establishing cooperative relationships between supporting components in schools, making visits to the homes of students with problems.Keywords: Strengthening Character Education, Teachers, Counseling GuidanceÂ Abstrak: Penelitian ini bertujuan untuk mengetahui (1) peran guru bimbingan konseling dalam memberikan penguatan pendidikan karakter. (2) kendala yang dihadapi bimbingan konseling dalam memberi penguatan. (3). upaya yang dilakukan bimbingan konseling untuk mengatasi kendala dalam memberi penguatan di SMA Negeri 1 Kalabahi. Penelitian ini menggunakan metode kualitatif deskriptif. Subjek penelitian ini adalah guru bimbingan konseling, kepala sekolah, dan siswa. Teknik pengumpulan data yang digunakan adalah observasi, wawancara, dan dokumentasi. Data dianalisis dengan menggunakan langkah-langkah reduksi data, display data, dan penarikan kesimpulan. Teknik pemeriksaan keabsahan data dengan menggunakan triangulasi sumber. Hasil penelitian menunjukkan bahwa (1) Peran guru bimbingan konseling dalam penguatan pendidikan karakter dimulai dari perencanaan kegiatan pemberian layanan bimbingan, pelaksanan program bimbingan dan konseling dengan menerapkan bentuk layanan, dan kegiatan evaluasi program layanan bimbingan dan konseling. (2) Kendala yang dihadapi yaitu kurangnya kerjasama antara kompnen-konponen yang ada di sekolah, kurangnya kerjasama antara guru BK dengan orang tua/wali, kurangnya rasa sukarela guru bimbingan dan konseling dalam melaksanakan tugas dan tanggung jawabnya, kurang jujur atau terbuka dari siswa atas masalah yang dihadapi. (3) Upaya yang dilakukan yaitu menjalin hubungan kerjasama antara komponen penunjang dalam sekolah, mengadakan kunjungan ke rumah siswa yang bermasalah.Kata kunci: Penguatan Pendidikan Karakter, Guru, Bimbingan Konseling